Strategy For Enhancing Digital Literacy to Support the Development of Sibetan Tourism Village as A Smart Village in Karangasem Regency - Ni Kadek Pande Aristiani; I Putu Sudana; Ni Putu Ratna Sari (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study examines strategies for enhancing digital literacy to support the development of Sibetan Tourism Village as a smart village in Karangasem Regency. The trend of increasing tourism villages is now accompanied by the development of digital villages as a national priority program. Smart villages aim to improve the quality of life for communities through digital literacy and technology. Although Sibetan Tourism Village has natural, cultural, and creative economic potential, the optimization of technology and digitalization has not yet been achieved. Using digital marketing theory, the concept of digital literacy, the smart village concept, and the tourism village concept, this study aims to formulate strategies and programs to enhance digital literacy in Sibetan Tourism Village. This research uses observation, interviews, and focus group discussions, and is analyzed using qualitative descriptive methods, IFE, EFE, and SWOT. The results show that based on the IFE matrix, the internal factor that is the main strength of Sibetan Tourism Village is infrastructure and internet network with a score of 0.37. The main weakness is the absence of digital-based innovation in the development of Sibetan Tourism Village with a score of 0.05. Based on the EFE matrix, the external factor that is the main opportunity for Sibetan Tourism Village is the development of alternative or sustainable tourism with a score of 0.42. The main threat to Sibetan Tourism Village is dependence on digital technology with a score of 0.06. The main strategies based on the IE matrix that can be implemented in Sibetan Tourism Village are market penetration strategies and product development strategies. From the SWOT matrix analysis, eight strategies were obtained with programs formulated for each strategy.